PENGARUH KONSENTRASI DAN LAMA PERENDAMAN ATONIK TERHADAP PERKECAMBAHAN BENIH ROTAN JERNANG (Daemonorops draco Blume.) - Betty Purwati; Hutami Indah Pertiwi; Bakti Mandala (Jurnal Informatika, Sistem Informasi dan Kehutanan (FORSINTA), 2024)
Jernang rattan is produced from a palm species surface layer of fruit by resine with dark red. Jernang rattan cultivation has several obstacles due to limiteation of seed availability, low seed production, and has technical problems in the form of hard fruit skin. This study aimed to studied the effect of the interaction of atonic concentration and soaking time for jernang rattan seeds on their germination. There were two factors in this study: Atonic concentration treatment (5 levels) and soaking time (3 levels). The results show that increasing the germination of Jernang rattan seeds can be done using an atonic concentration of 15 ppm and soaking for 1 hour. This is because it provides better results on research variables.